Rediscovering Religion and Secularism: A Critique of a Critique - Shihade, Magid (Archīum Ateneo, 2016)
In this paper, I will discuss the academic critique of secularism that is emanating from Western academic discourse and some of its limitations. I will also discuss how this scholarly critique of secularism has been used in Palestine, among other places, to defend symbolic as well as real repressive social norms within Muslim societies, and to defend the call for creating an Islamist state. This discussion is to be taken in the context of the Arab Spring, where political Islamist movements that embody fantasies about a certain past are calling for a return to a “real,” “non-secular,” “Islamic” state. Both such academic and political arguments base their analyses and arguments on false assumptions—epistemological as well as historical. My paper will attempt to discuss these assumptions and propose a possible political future that does not dichotomize secularism, religion, and politics, while drawing evidence from within Islamic knowledge on the rational rather than religious approach to organizing societies and states.